The Influence of Brand Image and Service Quality on Purchasing Decisions through Loyalty - Muchtar, Ardiansyah AR.; Khaddapi, Muammar; Tahier, Ilham (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to analyze the influence of brand image and awareness on purchasing decisions at Romeo Bouquet Atelier, using service quality as an intervening variable. The study used a quantitative approach. The population is consumers at Romeo Bouquet Atelier. A sample of 165 Romeo Bouquet Atelier consumers was taken using probability sampling using a questionnaire data collection method. The data processing technique used SEM PLS 3 statistical software. The results of the study indicate that brand image has a positive and significant direct effect on loyalty but is not significant on purchasing decisions. Service quality has a positive and significant effect on loyalty but is not significant on purchasing decisions. Loyalty has a positive and significant effect on purchasing decisions. Brand image and service quality have a positive and significant effect on purchasing decisions through loyalty as an intervening variable. This study is limited to Romeo Bouquet Atelier, which may restrict generalizability to other industries. The cross-sectional design captures data at one point in time, potentially overlooking behavioral changes. Additionally, the study focuses only on brand image, service quality, and loyalty, excluding other possible factors like pricing or promotions. Future research should explore a broader scope, include more variables, and consider longitudinal analysis. This study contributes to marketing and consumer behavior research by highlighting the role of brand image, service quality, and loyalty in purchasing decisions. It benefits business practitioners, especially in the luxury and floral industry, by emphasizing the importance of customer loyalty. Additionally, it serves as a reference for academics, researchers, and policymakers in developing effective brand and service strategies.